Upaya Guru PAI dalam Meningkatkan Evaluasi Ranah Afektif pada Siswa SMP N 12 Surakarta - Azzahroh, Husna Syifa; Nadifa, Haya Ula; Rochmah, Arfayza Maulia; Amanina, Nilna; Inayati, Nurul Latifatul (TSAQOFAH, 2025)
Islamic Religious Education aims to create learners who are moral and God-fearing. To measure the achievement of the objectives of Islamic religious education needs an evaluation process. The evaluation process consists of 3 domains, namely Cognitive, Affective, and psychomotor. However, this affective realm often reaps gaps, even though the evaluation of this affective realm is quite important to support the achievement of the goals of Islamic Religious Education. The method used in this study is a qualitative approach that is used to determine or describe the reality of the events examined so as to facilitate obtaining objective data. In this study, data collection was carried out by triangulation, which is a combination of interview techniques, observation, and documentation that makes one of the PAI teachers at SMPN 12 Surakarta as an object of research. Exploration of several new method innovations to succeed the evaluation of Pai learning from the affective sphere. These innovations were initiated by Pai teachers at SMPN 12 Surakarta because they had experienced obstacles and difficulties in using the previous evaluation method. The innovation of the PAI affective learning evaluation method in SMPN 12 Surakarta has so far run smoothly and is quite effective to measure the achievement of Pai learning. The learning evaluation process in SMPN 12 Surakarta emphasizes the importance of the role of teachers as evaluators to ensure the success of education, especially PAI. This evaluation not only focuses on academic values, but also includes affective domains such as attitudes, morals and adherence to religious teachings. SMPN 12 Surakarta not only measures the final result by scoring but also forms morals to Allah SWT as a reference in achieving holistic PAI goals.